2010
DOI: 10.1017/s0022112010000595
|View full text |Cite
|
Sign up to set email alerts
|

Extended self-similarity works for the Burgers equation and why

Abstract: Extended self-similarity (ESS), a procedure that remarkably extends the range of scaling for structure functions in Navier–Stokes turbulence and thus allows improved determination of intermittency exponents, has never been fully explained. We show that ESS applies to Burgers turbulence at high Reynolds numbers and we give the theoretical explanation of the numerically observed improved scaling at both the IR and UV end, in total a gain of about three quarters of a decade: there is a reduction of subdominant co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 32 publications
5
50
0
Order By: Relevance
“…4(b) for completeness. Similar to what is observed for the scaling behavior evidenced above through the MM, we consider also these types of results to be consistent with the interpretation proposed by [27], which can explain the ESS of variables that do not necessarily satisfy Burger's equation [34].…”
Section: A Bentheimer Sandstonesupporting
confidence: 90%
See 1 more Smart Citation
“…4(b) for completeness. Similar to what is observed for the scaling behavior evidenced above through the MM, we consider also these types of results to be consistent with the interpretation proposed by [27], which can explain the ESS of variables that do not necessarily satisfy Burger's equation [34].…”
Section: A Bentheimer Sandstonesupporting
confidence: 90%
“…With reference to ESS, a theoretical basis for Eq. (3) and its validity for all investigated lags has been provided with reference to (a) the one-dimensional Burger equation [34], (b) TFBM or TFGN [18], and (c) sub-Gaussian random processes subordinated to TFBM or TFGN [27].…”
Section: Scaling Of Statisticsmentioning
confidence: 99%
“…"In spite of several attempts to explain the success of ESS" cited by Chakraborty et al (2010) the authors note that "the latter is still not fully understood and we do not know how much we can trust scaling exponents derived by ESS. It would be nice to have at least one instance for which ESS not only works, but does so for reasons we can rationally understand."…”
Section: Introductionmentioning
confidence: 99%
“…Chakraborty et al (2010) cite the success of ESS in extending observed scaling ranges, and thus allowing more accurate empirical determinations of the functional exponent ξ(q) for turbulent velocities. ESS has been reported to achieve similar results for diffusion-limited aggregates, natural images, kinetic surface roughening, fluvial turbulence, sand wave dynamics, Martian topography, river morphometry, gravel-bed mobility and atmospheric barometric pressure, low-energy cosmic rays, cosmic microwave background radiation, metalinsulator transition, irregularities in human heartbeat time series, turbulence in edge magnetized plasma of fusion devices and turbulent boundary layers of the Earth's magnetosphere .…”
Section: Introductionmentioning
confidence: 99%
“…2) breaks down, it nevertheless includes numerous examples demonstrating this to be the case. In addition to the classic case of turbulent velocities (Chakraborty et al, 2010), these examples include geographical (e.g. Earth and Mars topographic profiles), hydraulic (e.g.…”
Section: Introductionmentioning
confidence: 99%